The meta-geography of the open society: An Auto-CM ANN approach. (1st June 2018) - Buscema, Massimo; Ferilli, Guido; Sacco, Pier Luigi
Highlights: We work on a dataset of five global public available indicators for year 2007. We use the AutoCM ANN to analyze multidimensional similarities among countries. We classify countries in terms of their orientation toward open society. We find that the meta-geography of the global order still reflects the colonialist rule. Abstract: This paper presents an innovative operationalization of world-system analysis through attributional data, and makes use of an innovative Artificial Neural Network computational tool, the Auto-Contractive Map (AutoCM), to analyze the core-periphery structure of a database including five well-known, publicly available indicators that can jointly be considered an empirical proxy of an open society formulation of Western governmentality: World Competitiveness Index; Freedom of Press Index; Economic Freedom Index; Corruption Perception Index; and UNDP Human Development Index. We find clear evidence of a core-periphery structure in the data, which is largely coherent with a benchmark version obtained through an alternative computational method, the Self-Organizing Map (SOM). Moreover, we find that the resulting meta-geography of the world-system is still shaped by the colonialist geopolitics of the British Commonwealth as the key organizational backbone.